PENERAPAN MODEL PBL DALAM PEMBELAJARAN STATISTIKA UNTUK MENGUKUR HASIL BELAJAR MATEMATIKA KELAS VIII SMPN 4 LUBUKLINGGAU - Maureta, Putri Sari; Pandra, Viktor; Mulyono, Dodik (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
Research conducted by class VIII SMP Negeri 4 Lubuklinggau aims to find out if after using the problem based learning method there is a significant increase. Research systems use semi-empirical methods. This research target is 26 students in class VIII, 11 boy or15 girl. Collection research information uses learning outcomes test of student' ability to solve statistical problems. The evidence of learning results is analyzed using quantitative analys. Research result show problem-based learning method will increase students' statistical learning efforts at SMP Negeri 4 Lubuklinggau. It was proven by the test results of 6,712 until Ho refused Ha accepted. Implementation problem-based learning method is almost complete. The value is reinforced by the fact that average post-test very large than pre-test value.